If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 1 + 5n + n Combine like terms: 5n + n = 6n 13 = 1 + 6n Solving 13 = 1 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 13 + -6n = 1 + 6n + -6n Combine like terms: 6n + -6n = 0 13 + -6n = 1 + 0 13 + -6n = 1 Add '-13' to each side of the equation. 13 + -13 + -6n = 1 + -13 Combine like terms: 13 + -13 = 0 0 + -6n = 1 + -13 -6n = 1 + -13 Combine like terms: 1 + -13 = -12 -6n = -12 Divide each side by '-6'. n = 2 Simplifying n = 2
| -1.25x-12.5=8.35 | | -1.25x-12.5=8.36 | | 3x-2x=1 | | 15=x+1 | | 6x*12=17 | | 5(2+4z)=85 | | 9-1=1 | | 2x-4y=8 | | 64=8(r+2) | | 4+2m=8 | | 3+5q=q+4q | | 3m+1=13 | | 98=-89 | | 3(n+4)+8=.5n | | 6(n+3)+12=12n | | 4(3-2x)=15 | | 2m-2=8 | | 6(n+3)=n-12 | | 16x-4=4x+2+2x+4 | | -4a+5-2a-9=44 | | 0.5y+5.2=-2.8 | | -3y-5=10 | | a-55=-17 | | 9=7z-13z-21 | | 2m+1=7 | | 5x+10-6x-2=13 | | 9x+5-x=4x+3 | | 8-k+2(4-2k)=k+2k | | s-19=-34 | | y+y+1+y+2=3y+3 | | 7-3=-17 | | 2x+3x=10 |